2015
DOI: 10.1007/s00125-015-3652-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of fibroblast growth factor 21 with baseline and new on-study microvascular disease in the Fenofibrate Intervention and Event Lowering in Diabetes study

Abstract: Aims/hypothesis Baseline circulating fibroblast growth factor 21 (FGF21) levels can predict total cardiovascular disease events in the Fenofibrate Intervention and Event Lowering in Diabetes (FIELD) study. This paper describes the relationship of baseline FGF21 levels and new on-study microvascular disease in patients with type 2 diabetes from the FIELD study. Methods Baseline FGF21 levels were measured in plasma by enzyme-linked immunosorbent assay in 9697 study participants. Total microvascular disease was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
1
24
1
Order By: Relevance
“…[16][17][18][19][20][21][27][28][29] In this analysis, as specified for all FIELD biomarker analyses, the primary cardiovascular outcome was on-trial total CVD events which was a composite of coronary heart disease (CHD) events, total stroke and other cardiovascular death events plus coronary and carotid revascularisation. 28 The secondary cardiovascular outcomes in this analysis were the individual components of total CVD events, that is, CHD event, total stroke, CVD mortality and coronary and carotid revascularisation. In this study, we also analysed the tertiary outcome of hospital admission for angina pectoris which included unstable angina, other forms of angina pectoris and unspecified angina pectoris with matched codes of I20.0, I20.8 and I20.9 by ICD-10 (International Classification of Diseases, Tenth Revision).…”
Section: Clinical Characteristics and Outcome Eventsmentioning
confidence: 99%
“…[16][17][18][19][20][21][27][28][29] In this analysis, as specified for all FIELD biomarker analyses, the primary cardiovascular outcome was on-trial total CVD events which was a composite of coronary heart disease (CHD) events, total stroke and other cardiovascular death events plus coronary and carotid revascularisation. 28 The secondary cardiovascular outcomes in this analysis were the individual components of total CVD events, that is, CHD event, total stroke, CVD mortality and coronary and carotid revascularisation. In this study, we also analysed the tertiary outcome of hospital admission for angina pectoris which included unstable angina, other forms of angina pectoris and unspecified angina pectoris with matched codes of I20.0, I20.8 and I20.9 by ICD-10 (International Classification of Diseases, Tenth Revision).…”
Section: Clinical Characteristics and Outcome Eventsmentioning
confidence: 99%
“…However, when those with microvascular disease were separately studied, serum FGF21 level was only correlated to nephropathy, and it had no association with retinopathy or other microvascular diseases. 20 A number of scholars further studied the relationship between serum FGF21 level and DR, and found that cases with DR had a significantly higher serum FGF21 level than those without DR. 17 21 Jung et al reported a different U-shaped relationship between serum FGF21 level and prevalence of DR. 22 This discrepancy might result from the difference in patients' characteristics, such as age, blood glucose level, lipoprotein level and so on. Numerous researches pointed out that the mentioned discrepancy might be related to a relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that higher baseline plasma FGF21 levels predict CV events in DM2 patients. Furthermore, Ong et al also found that higher baseline FGF21 levels established microvascular disease, and predicted the future development of new microvascular disease in a population of the FIELD study [19].…”
Section: Fgf21 and CV Prognosismentioning
confidence: 96%